EFL students’ perception of task-based reading with authentic text - Febri Dhany Triwibowo; Rahmanti Asmarani; Sarif Syamsu Rizal (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This research explores the integration of Task-Based Language Teaching (TBLT) with authentic texts in the Advanced Reading course to address the need for more contextual and critical approaches in EFL instruction. The research aims to examine how this combination enhances students’ critical thinking, contextual understanding, and engagement in reading activities. Employing a descriptive quantitative design supported by survey data from 49 students, the study analyzed learners’ perceptions after being exposed to TBLT using authentic materials. Findings reveal that 73.5% of students agreed that discussing authentic texts improved their critical thinking, 75% believed the TBLT approach enhanced communication and collaboration, and 77.5% felt more responsible for their own learning. However, 51.1% considered the method time-consuming and challenging. Overall, the integration of TBLT and authentic texts proved effective in promoting communicative competence, cultural awareness, and learner autonomy. The study concludes that authentic materials can create meaningful, real-world learning experiences when guided through task-based instruction. It recommends continuous teacher training and context-sensitive adaptation to optimize the implementation of TBLT in EFL classrooms.